The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ma15217761
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Sustainable Concrete with Partial Substitution of Cement with Red Mud: A Review

Abstract: Every year, millions of tons of red mud (RDM) are created across the globe. Its storage is a major environmental issue due to its high basicity and tendency for leaching. This material is often kept in dams, necessitating previous attention to the disposal location, as well as monitoring and maintenance during its useful life. As a result, it is critical to develop an industrial solution capable of consuming large quantities of this substance. Many academics have worked for decades to create different cost-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…In the meantime, the Rp of carbon steel B450C was ≈32 times lower in magnitude, and its initial value for the passive layer thickness of ≈0.1 nm tended to disappear. (7) The greater values of the passive layer thickness formed on SS430 and B450C steels during their exposure to the PC extract solution (previously reported) were ascribed to the more alkaline pH of that extract solution due to the higher content of Ca 2+ (in the absence of chloride ions), which was closely related to the greater Rp values of both steels compared to those obtained for the super sulfated (SS1) and sodium silicate modified limestone-Portland cement extract (JLSC1). (8) The reported results indicated that the change in time of pH and the free corrosion potential (OCP) values were decisively dependent on the cement composition and that of the ions' presence in the extract solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meantime, the Rp of carbon steel B450C was ≈32 times lower in magnitude, and its initial value for the passive layer thickness of ≈0.1 nm tended to disappear. (7) The greater values of the passive layer thickness formed on SS430 and B450C steels during their exposure to the PC extract solution (previously reported) were ascribed to the more alkaline pH of that extract solution due to the higher content of Ca 2+ (in the absence of chloride ions), which was closely related to the greater Rp values of both steels compared to those obtained for the super sulfated (SS1) and sodium silicate modified limestone-Portland cement extract (JLSC1). (8) The reported results indicated that the change in time of pH and the free corrosion potential (OCP) values were decisively dependent on the cement composition and that of the ions' presence in the extract solution.…”
Section: Discussionmentioning
confidence: 99%
“…The two of the most common alternative types of cement include: (a) blended cement, in which PC is partially replaced by one or more supplementary cementitious materials (limestone, blast furnace slag, fly ash, calcinated clays, natural pozzolan, waste glass, etc.) [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]; and (b) alkali-activated cement (AAC), based on the reaction of a precursor (i.e., the supplementary cementitious materials referred above, limestone, etc.) and alkaline activators (alkali silicates and/or hydroxides) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic studies conclude that red mud reacting with water molecules releases OHions contributing to high pH. With suitable treatment methods, red mud can be converted into cementitious material and used in the construction industry [1]. As per the studies, red mud calcined…”
mentioning
confidence: 82%
“…Therefore, it is urgent to find alternative materials or materials that can partially replace fly ash. (Al-Hashem et al, 2022) proposed using metakaolin as a substitute material for cement and conducted research on its mechanics and durability, suggesting that metakaolin may be a potential substitute material for concrete (Qureshi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%